Incidence, pattern and factors associated with home accidents among the elderly in Wattala Medical Officer of Health area, Sri Lanka - Rasika Nilanthie Jayasekera; Chrishantha Abeysena (College of Community Physicians of Sri Lanka, 2018)
Background: Good health is essential for older people to remain independent and to play a significant role in the family as well as in the community. Home accident is one that causes significant morbidity and mortality in the elderly population and a burden to the family and country. Objective: To determine the incidence and factors associated with home accidents among elders aged 60 years and above in Wattala Medical Officer of Health (MOH) area Methods: This was a cross-sectional study carried out among 884 elderly persons selected using cluster sampling method. An interviewer-administered questionnaire was used to collect data. Multiple logistic regression was applied to calculate adjusted odds ratio and 95% CI. Results: The incidence of home accidents among the elderly during past one month was 10.9% (95% CI=8.7, 13.1). It was 16.4% (95% CI=4.8, 27.9) among those aged 75 years and above and 8.9% (95% CI=6.5, 11.3) between 60 to 74 years. The sex-specific incidence of home accidents was 11.2% (95% CI=7.5, 14.8) among females and 10.4% (95% CI=5.1, 15.6) among males. Of the 96 home accidents, most were due to falls at the same level (n=40, 41.7%); occurred between 8.00 am to 12 noon (n=27, 28.1%) and between 4.00 pm to 8.00 pm (n=26, 27.1%); and took place in bed room (n=35, 36.5%). Among the victims, 80 (83.3%) had an injury most commonly on the head and neck area (n=33, 41.7%). The majority received treatment from general practice (89.6%) and out-patient department of private hospitals (52.4%). Presence of hypertension (OR=1.96; 95% CI=1.3, 3.0), arthritis (OR=2.4; 95% CI=1.5, 3.8) and difficulty in the mobility of upper part of the body (OR=2.2; 95% CI=1.3, 3.9) were significant factors associated with the occurrence of home accidents after adjusting for confounders. Conclusions: Awareness programs should be conducted on home accidents for caregivers especially caring for elders with physical disabilities.